Data-Based Information System Management in Improving the Quality of Junior High School Education - Budi Mulyadi; Hanafiah Hanafiah (Journal of Science and Education (JSE), 2026)
The imperative of digital transformation in education requires adaptive and evidence-based institutional governance. This study aims to critically and thoroughly analyze the managerial process of data-based information systems (DBIS) in efforts to improve the quality of education in junior high schools (SMP). Using a qualitative approach with a case study design at SMPN 1 Sukanagara and SMPN 1 Sukaresmi, this study explores the implementation of management functions—planning, organizing, executing, and controlling (POAC)—in a digital context. Data were collected through in-depth interviews with the principal, vice principal, operators, and teachers, supported by participatory observation and documentation studies. Data analysis was conducted interactively following the Miles and Huberman model. The results of the study show three main findings. First, the planning and organization of MSIBD in both schools is contextual, with SMPN 1 Sukanagara adopting a pragmatic-adaptive approach while SMPN 1 Sukaresmi implementing a visionary-integrative strategy, both based on participatory needs analysis. Second, the effective implementation of the system transformed administrative work processes to be more efficient and accurate, and became a catalyst for a shift in organizational culture towards data-driven decision making. Third, the dynamic monitoring process, despite facing challenges of digital literacy and infrastructure limitations, was successfully overcome through adaptive strategies that reflected the continuous improvement cycle (PDCA). This study concludes that the success of MSIBD is not only determined by technological sophistication, but also by managerial process maturity, supportive leadership, and the organization's capacity to learn and adapt.